2012
DOI: 10.3138/cmlr.68.2.164
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sentence Writing on Second Language French and Korean Lexical Retention

Abstract: This study investigates the effects of sentence writing (SW) on second language (L2) lexical retention by comparing two word-learning conditions: writing new words in sentences and repeated word-picture viewing. L2 learners of French and Korean attempted to learn 24 new words: 12 words with one condition and 12 words with another condition. Dependent measures were one immediate and two delayed posttests that required participants to produce target word forms. Results for both language groups revealed negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The sample lesson also limits forced semantic elaboration, or different ways of elaborating on the (redundant L1‐based) meaning of target words, such as writing target words in original sentences or reflecting on the (L1‐based) meanings of target words, during the initial stages. This provision is supported by research demonstrating large negative effects of semantically‐oriented tasks, such as writing target words in original sentences, on learning new word forms (e.g., Wong & Pyun, ).…”
Section: Commentarymentioning
confidence: 79%
See 3 more Smart Citations
“…The sample lesson also limits forced semantic elaboration, or different ways of elaborating on the (redundant L1‐based) meaning of target words, such as writing target words in original sentences or reflecting on the (L1‐based) meanings of target words, during the initial stages. This provision is supported by research demonstrating large negative effects of semantically‐oriented tasks, such as writing target words in original sentences, on learning new word forms (e.g., Wong & Pyun, ).…”
Section: Commentarymentioning
confidence: 79%
“…Research on lex‐IP has informed us about the effects of a variety of different tasks and learning conditions, providing the foundation of the IBI approach. Research in this area has demonstrated (a) negative effects of writing new L2 words in original sentences (e.g., Wong & Pyun, ), which supports Principle 7, and (b) negative effects of copying new words, which support Principle 6 (Barcroft, ). Many of the research findings that support Principle 7 run counter to predictions made by the ILH about the potential benefits of semantic evaluation of words and Nation's suggestion regarding the use of deeper processing activities.…”
Section: Evaluating the Ibi Approachmentioning
confidence: 98%
See 2 more Smart Citations
“…These findings are consistent with the TOPRA model's prediction that increased semantic processing can decrease word form learning and, to the extent that it was a factor, the mapping component of L2 vocabulary learning as well. 4 In two other studies, Barcroft (2004) and Wong and Pyun (2012) found that requiring learners to write target L2 words in sentences strongly diminished their intentional word learning when compared to no-task mapping conditions. Barcroft (2004) found that the sentence-writing condition decreased picture-to-L2 cued recall scores from 9.64 to 4.40 (Experiment 1; maximum 5 12) and from 10.30 to 4.95 (Experiment 2; maximum 5 12) as compared to no-sentence-writing conditions when English speakers attempted to learn L2 Spanish words.…”
Section: Previous Research On the Topra Modelmentioning
confidence: 96%